Effectiveness of a lifestyle intervention led by female community health volunteers versus usual care in blood pressure reduction (COBIN): an open-label, cluster-randomised trial. Issue 1 (January 2018) - Neupane, Dinesh; McLachlan, Craig S; Mishra, Shiva Raj; Olsen, Michael Hecht; Perry, Henry B; Karki, Arjun; Kallestrup, Per
Summary: Introduction: Elevated blood pressure greatly contributes to cardiovascular deaths in low-income and middle-income countries. We aimed to investigate the effectiveness of a population-level intervention led by existing community health workers in reducing the burden of hypertension in a low-income population. Methods: We did a community-based, open-label, two-group, cluster-randomised controlled trial in Nepal. Using computer-generated codes, we randomly assigned (1:1) 14 clusters to a lifestyle intervention led by female community health volunteers (FCHVs) or usual care (control group). In the intervention group, 43 FCHVs provided home visits every 4 months for lifestyle counselling and blood pressure monitoring. Eligible participants had been involved in a previous population-based survey, were aged 25–65 years, did not have plans to migrate outside the study area, and were not severely ill or pregnant. The primary outcome was mean systolic blood pressure at 1 year. We included all participants who remained in the trial at 1 year in the primary analysis. This trial is registered withClinicalTrials.gov, numberNCT02428075 . Findings: Between April 1, 2015, and Dec 31, 2015, we recruited 1638 participants (939 assigned to intervention; 699 assigned to control). At 1 year, 855 participants remained in the intervention group (425 were normotensive, 175 were prehypertensive, and 255 had hypertension) and 613 remained in the control group (305 were normotensive, 128 were prehypertensive, and 180 had hypertension). The mean systolic blood pressure at 1 year was significantly lower in the intervention group than in the control group for all cohorts: the difference was −2·28 mm Hg (95% CI −3·77 to −0·79, p=0·003) for participants who were normotensive, −3·08 mm Hg (–5·58 to −0·59, p=0·015) for participants who were prehypertensive, and −4·90 mm Hg (–7·78 to −2·00, p=0·001) for participants who were hypertensive. Interpretation: A simple, FCHV-led lifestyle intervention coupled with monitoring of blood pressure is effective for reduction of blood pressure in individuals with hypertension and ameliorates age-related increases in blood pressure in adults without hypertension in the general population of Nepal. Funding: Aarhus University, Jayanti Memorial Trust.